Contact forces in Brazil nut effect phenomenon of boulders on the asteroid surface. (April 2020) - Rozzykin, A Z; Dermawan, B; Viridi, S
Abstract: Granular particles can be found on the asteroids in the form of regolith. Regolith is a pile of boulders and gravels that covers the surface of an asteroid and have various sizes. Brazil Nut Effect (BNE) is one of the well-known phenomena that happened in this sort of system. This phenomenon leads to occur a tendency for larger boulders to come up to the surface. Some asteroids like Eros and Itokawa show that BNE supposes to happen also in a low gravity environment. BNE in asteroid may be generated by seismic vibration that causes inter-particle collisions. The collisions are represented by contacts among particles, so that contact forces need to be counted in modeling BNE. This study aims to build a modeling of BNE in asteroid involving contact forces caused by inter-particle collisions during the seismic vibration. This study shows that contact forces have a positive role in BNE by inter-particle contacts. The contacts accommodate the system to keep larger boulders staying in the elevated height. In the model that only involves static friction (without rolling), the vector of normal forces dominates over the tangential one for the resultant forces. Uprising of the larger boulders has been observed in the simulation, but most of them are still buried underneath the smaller ones. It is predicted that a seismic vibration with large enough energy is needed to make all of the larger boulders to come up to the surface. With that result, the larger boulders observed on the surface of some asteroids nowadays are reasonably the result of BNE which caused by heavy bombardment by meteoroids in the early stage of Solar System formation that drives some high-energy seismic vibration.